Mass spectra of some azomethines of 5-amino-2-phenylindole series - Tai, Dang Nhu; Thanh, Nguyen Dinh; Nam, Pham Duy; Duc, Hoang Thanh (Vietnam Journal of Chemistry, 2014)
The mass spectra of some azomethines of 5-amino-2-phnylindole have been recorded and their structures have been elucidated. The general fragmentations of these azomethines in mass spectra were suggested and discussed. It has shown that the main direction of fragmentation was the cleavage of C–N bond between indole ring and azomethine bond –CH=N– lead to form fragment ion at m/z 192 (direction A).